2016
DOI: 10.1002/jsfa.7578
|View full text |Cite
|
Sign up to set email alerts
|

p‐Coumaric acid and its conjugates: dietary sources, pharmacokinetic properties and biological activities

Abstract: p-Coumaric acid (4-hydroxycinnamic acid) is a phenolic acid that has low toxicity in mice (LD50 = 2850 mg kg(-1) body weight), serves as a precursor of other phenolic compounds, and exists either in free or conjugated form in plants. Conjugates of p-coumaric acid have been extensively studied in recent years due to their bioactivities. In this review, the occurrence, bioavailability and bioaccessibility of p-coumaric acid and its conjugates with mono-, oligo- and polysaccharides, alkyl alcohols, organic acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
302
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(314 citation statements)
references
References 118 publications
(88 reference statements)
4
302
1
7
Order By: Relevance
“…However, much fewer forms are conjugated and these are slowly absorbed in the upper gastrointestinal tract. Their high biological activities but low absorption remain a puzzle for scientists …”
Section: Resultsmentioning
confidence: 99%
“…However, much fewer forms are conjugated and these are slowly absorbed in the upper gastrointestinal tract. Their high biological activities but low absorption remain a puzzle for scientists …”
Section: Resultsmentioning
confidence: 99%
“…In mice, oral administration of a dose up to 5000 mg/kg was also found to be safe [77]. Compared to gallic acid, p-coumaric acid exhibited low toxicity with LD 50  ~ 2850 mg/kg body weight [78]. In conclusion, the safety and toxicity profiles of phenolic compounds vary depending upon their structure, route of administration and the animals that are being studied.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…A dietary phenolic compound, p ‐coumaric acid ( p ‐CA; 3‐[4‐hydroxyphenyl]‐2‐propenoic acid), is also biotechnologically concerning as a precursor for different flavonoids like resveratrol and naringenin . p ‐CA is pharmacokinetically absorbed rapidly in intestine and has higher bioavailability along with low toxicity compared with other phenolic compounds . Many investigators have shown that supplemental p ‐CA exhibits various bioactivities, including antioxidant, anti‐inflammatory, anti‐ulcer, and anti‐diabetic activities .…”
Section: Introductionmentioning
confidence: 99%